The encounter between Almada and the Tagus - Carvalho, Isadora Bento de (2022)
The relationship that Almada developed with the Tagus river became vital to the growth and development of the territory, shaping its character and identity. This connection was established through the city’s margins – a physical connection – and by its verticality – a visual connection, allowing the city to become part of trade routes connecting its margins with the world as well as giving Almada its reputation as the ‘Miradouro’ over both the Tagus and Lisbon. This relationship, which is dynamic and susceptible to changes, had its peak with the industrialisation of the margins during the 20th century and has, ever since, declined. Almada’s riverside is currently an obsolete territory, a memory of its glorious industrial past, weakening the city’s connection with its river. Focusing on Almada’s physical and visual connection with the Tagus, this dissertation intends to form a clear understanding of the development of this relationship over time and its crucial role in the city’s spatial organisation. Using primary sources such as cartographies, historical descriptions and iconographies, an analysis was conducted to illustrate the morphological changes in the river margins. These changes unfolded through the construction of artificial ground, not only characterising the conquest of Almada over the Tagus – but also considering the possible rise of sea levels in the future due to climate change – suggesting the reconquest of Tagus over Almada. The neglected platform where Lisnave once operated becomes ground for an hipotesis of intervention, allowing the reconnection of the city with the river, both physically and visually. This thesis seeks to investigate how the implementation of horizontal and vertical architectural elements can help re-establish this lost connection and celebrate Almada’s encounter with the Tagus.